Prevalence and Factors Associated with Prosthetic Joint Infections in Patients with Staphylococcus aureus Bacteraemia: A 7-Year Retrospective Study - Matthaios Papadimitriou-Olivgeris; Laurence Senn; Claire Bertelli; Bruno Grandbastien; Sylvain Steinmetz; Noémie Boillat-Blanco (MDPI AG, 2022)
Background: Staphylococcus aureus is the main cause of haematogenous prosthetic joint infections (PJI). We aimed to describe the prevalence and factors associated with PJI in patients with documented S. aureus bacteraemia. Methods: Adult patients with S. aureus bacteraemia and presence of prosthetic joint hospitalized in Lausanne University Hospital during a seven-year period (2015-2021) were included. Results: Among 135 patients with S. aureus bacteraemia and prosthetic joints, 38 (28%) had PJI. Multivariate analysis revealed that the presence of PJI was associated with knee arthroplasty (P 0.029; aOR 3.00, 95% CI 1.12-8.05), prior arthroplasty revision (P 0.034; aOR 3.59, 95% CI 1.10-11.74), community-acquired bacteraemia (P 0.005; aOR 4.74, 95% CI 1.61-14.01) and age < 70 years (P 0.007; aOR 9.39, 95% CI 1.84-47.85). Conclusions: PJI was common among patients with documented S. aureus bacteraemia. PJI was associated with characteristics of the prosthesis, such as prior arthroplasty revisions and knee prosthesis.